Cysteine Depletion Causes Oxidative Stress and Triggers Outer Membrane Vesicle Release by Neisseria meningitidis; Implications for Vaccine Development - van de Waterbeemd, Bas (Public Library of Science, 2013)
Outer membrane vesicles (OMV) contain immunogenic proteins and contribute to in vivo survival and virulence of bacterial pathogens. The first OMV vaccines successfully stopped Neisseria meningitidis serogroup B outbreaks but required detergent-extraction for endotoxin removal. Current vaccines use attenuated endotoxin, to preserve immunological properties and allow a detergent-free process. The preferred process is based on spontaneously released OMV (sOMV), which are most similar to in vivo vesicles and easier to purify. The release mechanism however is poorly understood resulting in low yield. This study with N. meningitidis demonstrates that an external stimulus, cysteine depletion, can trigger growth arrest and sOMV release in sufficient quantities for vaccine production (±1500 human doses per liter cultivation). Transcriptome analysis suggests that cysteine depletion impairs iron-sulfur protein assembly and causes oxidative stress. Involvement of oxidative stress is confirmed by showing that addition of reactive oxygen species during cysteine-rich growth also triggers vesiculation. The sOMV in this study are similar to vesicles from natural infection, therefore cysteine-dependent vesiculation is likely to be relevant for the in vivo pathogenesis of N. meningitidis.